Pleural flaps in the treatment of recurrent tracheoesophageal fistula - Raymond W.J. Ho; Ammar Alazki; Steffan Loff (Elsevier, 2022)
A trachea-oesophageal fistula (TEF) is commonly observed in Oesophageal Atresia (EA). Surgical intervention is required to achieve continuity in the digestive tract. Recurrent trachea-oesophageal fistula (rTEF) is a common complication of EA Repair. This paper describes the feasibility of using pleura flaps to treat the mentioned complication. We present 3 cases encountered between 2019 and 2020 in our institution.